Kondisi Makro Ekonomi Terhadap Hasil Investasi Asuransi Jiwa Syariah di Indonesia - Firsty Dzanurrahmana Zein; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This research attempt to analyze the effect of variable inflation, Rupiah exchange rate, and gross domestic product towards investment result of sharia life insurance in Indonesia period 2012:Q1 until 2016:Q1. This research using quantitative methods. The analysis techniques used is multiple linear regression with data panel and significance level of 0,05. The approach used in this research is Random Effect Model. The result of t-test, gross domestic bruto has a significant influence to investment result of sharia life insurance with 0,0459. Inflation and Rupiah exchange rate has not significant influence to investment result of sharia life insurance. However, inflation, Rupiah exchange rate and gross domestic product simultaneously provide a significant effect to Investment result of sharia life insurance.